The French-Canadian Idea of Confederation, 1864-1900. - Silver, A. I. (University of Toronto Press, 2014)
At Confederation, most French Canadians felt their homeland was Quebec; they supported the new arrangement because it separated Quebec from Ontario, creating an autonomous French-Canadian province loosely associated with the others.